Animal Toxins as Therapeutic Tools to Treat Neurodegenerative Diseases - de Souza, Jessica M.; Goncalves, Bruno D. C.; Gomez, Marcus V.; Vieira, Luciene B.; Ribeiro, Fabiola M. (Frontiers in Pharmacology, 2018)
Neurodegenerative diseases affect millions of individuals worldwide. So far, no disease-modifying drug is available to treat patients, making the search for effective drugs an urgent need. Neurodegeneration is triggered by the activation of several cellular processes, including oxidative stress, mitochondrial impairment, neuroinflammation, aging, aggregate formation, glutamatergic excitotoxicity, and apoptosis. Therefore, many research groups aim to identify drugs that may inhibit one or more of these events leading to neuronal cell death. Venoms are fruitful natural sources of new molecules, which have been relentlessly enhanced by evolution through natural selection. Several studies indicate that venom components can exhibit selectivity and affinity for a wide variety of targets in mammalian systems. For instance, an expressive number of natural peptides identified in venoms from animals, such as snakes, scorpions, bees, and spiders, were shown to lessen inflammation, regulate glutamate release, modify neurotransmitter levels, block ion channel activation, decrease the number of protein aggregates, and increase the levels of neuroprotective factors. Thus, these venom components hold potential as therapeutic tools to slow or even halt neurodegeneration. However, there are many technological issues to overcome, as venom peptides are hard to obtain and characterize and the amount obtained from natural sources is insufficient to perform all the necessary experiments and tests. Fortunately, technological improvements regarding heterologous protein expression, as well as peptide chemical synthesis will help to provide enough quantities and allow chemical and pharmacological enhancements of these natural occurring compounds. Thus, the main focus of this review is to highlight the most promising studies evaluating animal toxins as therapeutic tools to treat a wide variety of neurodegenerative conditions, including Alzheimer’s disease, Parkinson’s disease, brain ischemia, glaucoma, amyotrophic lateral sclerosis, and multiple sclerosis.